Kecukupan Pasteurisasi Sistem Kontinyu Krimer Kental Manis dan Pengaruhnya Terhadap Stabilitas Selama Penyimpanan - Anis Zamaluddien; Feri Kusnandar; Eko Hari Purnomo (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
A sweetened condensed creamer (SCC) is a well-known dairy-based product used in various food products. SCC has pH of 6.00 and water activity (aw) of less than 0.8. A pasteurization process is applied in SCC processing to inactivate potential pathogenic microorganism in order to yield safely consumed product with a long shelf-life. The aim of this study was to evaluate thermal process adequacy of SCC in a commercial scale continuous pasteurization at 85°C and 95°C. Thermal process adequacy was determined by comparing the pasteurization value (P) of the process with standardized P value at different D cycles (2D, 3D, and 6D) of targeted microorganism and lipase enzyme. Pasteurization process at both 85°C and 95°C satisfactorily inactivated targeted microorganism (vegetative cells, coliform, yeast and mould, Salmonella, S aureus, and L monocytogenes). However, the designed pasteurization did not sufficiently inactivate lipase enzyme. SCC processed at 85°C had a longer shelf-life in term of its viscosity (292.4 days) than that of pasteurized at 95°C (174.5 days). Keywords: pasteurization value, rheology, shelf-life, sweetened condensed creamer, thermal process DOI: https://doi.org/10.29244/jmpi.2019.6.108